2021
DOI: 10.3389/fmed.2021.741751
|View full text |Cite
|
Sign up to set email alerts
|

Enterocytozoon Bieneusi Infects Children With Inflammatory Bowel Disease Undergoing Immunosuppressive Treatment

Abstract: Objectives: Patients with inflammatory bowel disease (IBD) are susceptible to intestinal opportunistic infections due to both defective mucosal immunity and altered immune response resulting from immunosuppressive treatment. Microsporidia infecting the gastrointestinal tract and causing diarrhoea can potentially affect the course of IBD.Methods: Stool samples (90 IBD children and 121 healthy age-matched controls) were screened for Encephalitozoon spp. and Enterocytozoon bieneusi by microscopy and polymerase ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Enterocytozoon bieneusi is one of the common pathogens that causes chronic diarrhea in the human body, especially in people with immunodeficiency or low immunity (such as people with HIV, organ transplant recipients, bone marrow transplant recipients, patients with tumors, elderly people, and children) [ 83 , 94 , 100 ]. In the statistical analysis of people at different ages, compared with other groups, the infection rates of young people and the elderly were higher.…”
Section: Discussionmentioning
confidence: 99%
“…Enterocytozoon bieneusi is one of the common pathogens that causes chronic diarrhea in the human body, especially in people with immunodeficiency or low immunity (such as people with HIV, organ transplant recipients, bone marrow transplant recipients, patients with tumors, elderly people, and children) [ 83 , 94 , 100 ]. In the statistical analysis of people at different ages, compared with other groups, the infection rates of young people and the elderly were higher.…”
Section: Discussionmentioning
confidence: 99%
“…Microsporidia are increasingly appreciated to be ubiquitous in the environment and to infect host from all the animal taxa including humans (Stentiford et al, 2016). Indeed, a recent study identified a high prevalence (14.9%) of infection by the Microsporidian specie E. bieneusi among children with IBD treated with various immunosuppressants (Zajączkowska et al, 2021). The altered barrier functions of the epithelium characteristic of IBD (McCole, 2014) could contribute to a higher susceptibility to Microsporidian infections.…”
Section: Discussionmentioning
confidence: 99%